2020
DOI: 10.21037/atm-20-3299
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding of infants born to mothers with COVID-19: a rapid review

Abstract: Background: Existing recommendations on whether mothers with COVID-19 should continue breastfeeding are still conflicting. We aimed to conduct a rapid review of mother-to-child transmission of COVID-19 during breastfeeding.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 29 publications
0
28
0
5
Order By: Relevance
“…Infected mothers must continue taking suitable precautions to decrease the probability of virus transmission through close contact and droplets during breastfeeding. [14][15] Early and precise diagnosis of COVID-19 is fundamental to save people's lives. False negative test results could accelerate the spread of the disease in the community while false positive results could lead to starting unnecessary therapy and mental trauma to the patients and families.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Infected mothers must continue taking suitable precautions to decrease the probability of virus transmission through close contact and droplets during breastfeeding. [14][15] Early and precise diagnosis of COVID-19 is fundamental to save people's lives. False negative test results could accelerate the spread of the disease in the community while false positive results could lead to starting unnecessary therapy and mental trauma to the patients and families.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…This is because, even though the maternal showed positive towards SARS-CoV, the breast feeding without any protective measures showed negative COVID result on the infant. The same was denoted for the influenza virus detection but the authors ensure the distancing between the mother and infant as the impact of viral infection is not clear through investigation [51]. Similar to these reports, the studies by Lackey et al also did not trace the presence of SARS-CoV-2 in infants spread through breast milk but the vertical transmission was discussed [52].…”
Section: Human Coronavirus and Their Structuresmentioning
confidence: 89%
“…In our research, the infant was most likely infected by his mother, and we cannot rule out the possibility that the infant acquired his infection from breastfeeding. Thus far, the transmission of SARS−COV-2 from mother to child has been controversial [ 23 ]. Some researchers [ 24 , 25 ] have found that SARS−COV-2 is not transmitted to infants through breast milk, amniotic fluid or placenta, but other studies [ 9 , 26 ] have shown that antibodies and viral RNA can be detected in breast milk, which suggests a possible mother -to -child transmission of the virus.…”
Section: Discussionmentioning
confidence: 99%